Visual-Vestibular Rehabilitation Using Orthoptic and Vestibulo-Ocular Reflex Training in Parinaud Syndrome: A Case Report - jeyaraj, priyanka; Jayaraj, Vanitha; Suganthirababu, Prathap (Biomedical Sciences and Clinical Medicine, 2026)
Parinaud syndrome, or dorsal midbrain syndrome, is a rare neuro-ophthalmological disorder characterized by vertical gaze palsy, convergence-retraction nystagmus, light-near dissociation, and impaired convergence. Rehabilitation literature has primarily focused on motor outcomes in stroke, with limited evidence on visual rehabilitation in this Syndrome. A 39-year-old female presented with acute thalamic-midbrain hemorrhage and developed Parinaud Syndrome with vertical gaze palsy, convergence-retraction nystagmus, diplopia, and impaired near point of convergence. A structured visual-vestibular rehabilitation protocol was implemented, consisting of orthoptic training (pencil push-ups, stereogram fusion, saccadic tracking, smooth pursuits) and vestibulo-ocular reflex (VOR) training (gaze stabilization drills). The program was delivered for 4 weeks, 5 sessions per week. The patient showed partial restoration of upward gaze, improved convergence, reduced diplopia, and enhanced gaze stability. Near point of convergence improved, facilitating better reading ability and daily visual tasks with less fatigue. Functionally, she reported greater independence and confidence in activities requiring visual control. This case demonstrates the effectiveness of targeted visual-vestibular rehabilitation in Parinaud Syndrome, highlighting the role of orthoptic and vestibulo-ocular reflex exercises in improving ocular motility and functional vision. Future studies exploring digital eye-tracking and virtual reality may further enhance rehabilitation outcomes in this rare condition.